Control of quality factor in laterally coupled vertical cavities. Issue 3 (1st June 2020) - Chen, Si; Francis, Henry; Ho, Chih‐Hua; Wang, Yun‐Ran; Che, Kai‐Jun; Hopkinson, Mark; Jin, Chao‐Yuan
Abstract : In this work, the authors demonstrate the control of quality factor ( Q ‐factor) is laterally coupled vertical cavities. A 3 μm‐side‐length square cavity directly connected to a 1.5 μm‐width, 10 μm‐length Fabry–Perot (FP) cavity has been fabricated and measured. Dynamic tuning of the Q ‐factor has been successfully observed by bringing the square cavity and FP cavity into resonance. The vertical‐cavity‐based Q ‐factor control scheme provides a new choice for the modulation of light and holds potentials for applications associated with optical information processing.